2018
DOI: 10.1097/scs.0000000000004489
|View full text |Cite
|
Sign up to set email alerts
|

Algorithm for Airway Management in Patients With Pierre Robin Sequence

Abstract: The algorithm differs from previous ones in that it relies on rigorous pre- and post-intervention PSG (including with a nasopharyngeal airway), as well as that it allows flexibility between treatment options given the whole-patient clinical scenario and endoscopic findings. Results from these studies may be integrated to stratify patients into those who are most likely to benefit from conservative interventions or surgical procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 33 publications
0
33
0
2
Order By: Relevance
“…adolescents with Pierre Robin sequence -a cross-sectional study in a 72-patient series Béatrice Thouvenin 1,2 , Véronique Soupre 2,3 , Marie-Anne Caillaud 4 , Charlotte Henry-Mestelan 1 , Christel Chalouhi 1,2 , Bachar Houssamo 2,3 , Cécile Chapuis 3 , Katia Lind 1 , Aurélie Royer 1,2 , Nancy Vegas 1,2,5 , Jeanne Amiel 5,6,7 , Gérard Couly 3,7 , Arnaud Picard 2, 3,7 , Laurence Vaivre-Douret 5,7,8 , Véronique Abadie 1, 2,5,7,8 *…”
Section: Quality Of Life and Phonatory And Morphological Outcomes In Cognitively Unimpairedunclassified
See 1 more Smart Citation
“…adolescents with Pierre Robin sequence -a cross-sectional study in a 72-patient series Béatrice Thouvenin 1,2 , Véronique Soupre 2,3 , Marie-Anne Caillaud 4 , Charlotte Henry-Mestelan 1 , Christel Chalouhi 1,2 , Bachar Houssamo 2,3 , Cécile Chapuis 3 , Katia Lind 1 , Aurélie Royer 1,2 , Nancy Vegas 1,2,5 , Jeanne Amiel 5,6,7 , Gérard Couly 3,7 , Arnaud Picard 2, 3,7 , Laurence Vaivre-Douret 5,7,8 , Véronique Abadie 1, 2,5,7,8 *…”
Section: Quality Of Life and Phonatory And Morphological Outcomes In Cognitively Unimpairedunclassified
“…A family history of PRS is present in 10 to 15% of cases, possibly involving mutations upstream of the SOX9 gene, which participates in embryonic mandible development among other roles [4,5]. Neonates with PRS experience breathing and feeding issues, including upper airway obstruction due to the posterior position of the tongue and to glossopharyngeal/laryngeal hypotonia, suckling and swallowing difficulties and gastroesophageal reflux [6,7]. Because of these functional disorders, the first year of an infant with PRS is marked by many burdensome medical necessities, such as prolonged hospitalization, mother/child separation, nasogastric or gastrostomy tube feeding and the management of upper airway obstruction.…”
Section: Introductionmentioning
confidence: 99%
“…A family history of PRS is present in 10% to 15% of cases, possibly involving mutations upstream of the SOX9 gene, which participates in embryonic mandible development among other roles [ 4 , 5 ]. Neonates with PRS exhibit breathing and feeding issues, including upper airway obstruction due to the posterior position of the tongue and to glossopharyngeal/laryngeal hypotonia; sucking and swallowing difficulties; and gastroesophageal reflux [ 6 , 7 ]. Because of these functional disorders, the first year for an infant with PRS is marked by many burdensome medical necessities, such as prolonged hospitalization, mother/child separation, nasogastric or gastrostomy tube feeding and management of upper airway obstruction.…”
Section: Introductionmentioning
confidence: 99%
“…Polysomnography (PSG) is routinely used in the evaluation of obstructive sleep apnea (OSA) in patients with Pierre Robin Sequence (PRS) and associated tongue-based upper airway obstruction. 1-4 Previous studies have shown that mandibular distraction osteogenesis (MDO) for these patients can significantly improve OSA by lengthening the mandible and thereby increasing airway patency. 5-12 Comparison studies using post-distraction PSG have demonstrated the change in sleep architecture facilitated by this surgical intervention.…”
Section: Introductionmentioning
confidence: 99%